Three Names of Imagination - Sabolius, Kristupas (Religija ir kultūra, 2011)
The author works through phenomenological concept of imagination and its noetic function by analyzing three main ‘names’ found in Husserl’s description of die Phantasie: presentification, neutralization and modification. Although all these terms mean that objects are not given ‘in person’ or ‘bodily’ (leibhaftig) and refer to the ‘lack reality’, the closer examination of their status reveals that the latter characteristic of imagination is drawn from the intellectual perspective and, consequently, undergoes the rationalization of ‘reality perception’. But it is namely the active modification, registered in the field of perception as well, discloses the hidden layers of experience due to which the mode of actual situation could assume different levels of intensity.